Respiratory-related activation of human abdominal muscles during exercise - Abraham, Kirk A (Blackwell Science Inc, 2002)
We tested the hypothesis that abdominal muscles are active during the expiratory phase of the respiratory cycle during exercise. Electromyographic (EMG) activities of external oblique and rectus abdominis muscles were recorded during incremental exercise to exhaustion and during 30 min of constant work rate exercise at an intensity of 85 % of the peak oxygen consumption rate (V̇(O2)). High amplitude intramuscular EMG activities of both abdominal muscles could be evoked with postural manoeuvres in all subjects. During cycling, respiratory-related activity of the external obliques was evoked in four of seven subjects, whereas rectus abdominis activity was observed in six of the seven subjects. We measured only the activity that was confined exclusively to the expiratory phase of the respiratory cycle. Expiratory activity of both muscles increased with exercise intensity, although peak values averaged only 10-20 or 20-40 % of the peak activity (obtained during maximal, voluntary expiratory efforts) for the external oblique and rectus abdominis muscles, respectively. To estimate how much of the recorded abdominal muscle activity was supporting leg movements during exercise, we compared the activity at the very end of incremental exercise to that recorded during the first five respiratory cycles after the abrupt cessation of exercise, when ventilation was still very high. Although external oblique activity was reduced after exercise stopped, clear expiratory activity remained. Rectus abdominis activity remained high after exercise cessation, showing a gradual decline that approximated the decline in ventilation. During constant work rate exercise, EMG activities increased to 40-50 and 5-10 % of peak in rectus and external oblique muscles, respectively, and then plateaued for the remainder of the bout in spite of a continual upward drift in V̇(O2) and pulmonary ventilation. Linear regression analysis showed that the rise in respiratory-related expiratory muscle activity during progressive intensity exercise was significantly correlated with ventilation, although weakly. In constant work rate exercise, expiratory EMG activities increased, but the changes were highly variable and did not change as a function of exercise time, even though ventilation drifted significantly with time. These experiments suggest that abdominal muscles play a role in regulating the ventilatory response to progressive intensity bicycle exercise, although some of the observed activity may support postural adjustments or limb movements. The contribution of abdominal muscles to ventilation during constant work rate exercise is variable, and expiratory activity does not ‘drift’ significantly with time.